PERAN KONSTITUSI DALAM MENJAMIN KEDAULATAN NEGARA DAN HAK-HAK ASASI WARGA NEGARA - Lillah Ariani; Jingga Ajeng Muda Jamaica; Sahihah Anik Awalia; Ananda Putri Agustina Hikmawati (Bajang Institute, 2024)
Indonesia is a state of law. In the rule of law, the maintenance of nationality is governed by a constitution of law. The Constitution is the foundation of a country's legal system, which includes the protection of human rights. The constitution forms the framework that regulates the distribution of power between the institutions of the state, ensuring a balance of power essential to preventing abuse of power. Through constitutional mechanisms, the state not only affirms its sovereignty, but also ensures that the government runs fairly and democratically, and respects and protects the rights of its citizens. The Constitution guarantees the rights of the people, such as the right to associate, assemble and express opinions. Research methods involve literature analysis, case studies, as well as the application of normative methods. The results show that if you want to understand constitutionalism correctly, its history must be considered. Constitutionalism has developed historically. The Constitution demonstrates the sovereignty of the people and limits the power of the state. In accordance with constitutional provisions, the State must respect, fulfil, and protect human rights. Therefore, the role of the constitution in guaranteeing the sovereignty of the State and the rights of the citizens is very significant in ensuring the survival and well-being of the state